Guidelines for the formulation of public policy on employability and entrepreneurship (GEON Journal (Management, Organizations and Business), 2016)
The objective of this article is to establish what the main elements to be considered in the municipality of Puerto Gaitán to implement appropriate public policy employability and entrepreneurship that enables sustainable economic development for the city and especially for its inhabitants. To this it has been prevailing determine the main economic and social issues affecting the municipality, its causes and effects generated.Analyze this situation has allowed reflect on the issues that have led to this city in 2014 had a budget of fifty-eight thousand six hundred sixty-nine million nine hundred fifty four thousand pesos ($ 58,669,954,000) having such an index Unsatisfied Basic Needs of 40.05% for urban areas and 83.39% for the rural sector. Faced with this situation they have been raised a number of potential viable solutions, which have been named as "strategic lines". A total of six lines covering different strategies in order to be an alternative to optimize the use of available resources and improve the welfare of the population.
Keywords: Human Capital; Sources of Income; employability; Entrepreneurship; productive activities